College athletes' perceptions of social support provided by their coach before injury and after it - Malinauskas, R. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. The aim of this study was to evaluate athletes' perceptions of social support provided by their coach before injury and after it. Methods. Participants were 29 high school athletes with minor to severe injuries, who were forced to sit out practice or competition for at least 3 days due to their injury. Male (n=17) and female (n=12) team sport and individual sport athletes ranged in age from 18 to 25 years (mean: 21.18; standard deviation: 1.26). Eight subjects (28%) had major injuries, 12 (41%) had moderate injuries, and 9 (29%) had minor injuries. Twenty-nine high school athletes completed a modified version of the Social Support Survey. Data were collected on who provides each of 6 types of social support, how satisfied the high school athletes are with the amount and type of support they received, and the perceived effect of support on their well-being. Results. With two exceptions, results indicated no differences between preinjury and postinjury satisfaction with the support provided by coaches. The exceptions were for task challenge support and emotional challenge support. Results indicated no differences in the perceived importance to their well-being of support provided by coaches before injury and after it. The exceptions were for listening support and emotional support. Conclusion. These findings confirm the possible positive effects of coaches' listening and emotional support on injured high school athletes' recovery efforts.